2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24475
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Engineering Students’ Ability to Thrive in Diverse and Global Environments

Abstract: Engineering programs, professional associations, and industry stakeholders emphasize the importance of preparing graduates for an increasingly global, rapidly changing environment. Although there has been increased attention to prepare undergraduates for a global engineering profession, there are challenges associated with measuring how cultural programs and experiences contribute to positive changes in students' abilities to work and thrive in diverse environments. Global competency can be defined broadly as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Model 1, which includes all 390 students, indicates that female students are more likely to score higher than male students by 2.9 points on the MGUDS-S total score. This is consistent with previous research that found differences in intercultural competency scores by gender at the undergraduate level (Jesiek et al , 2012; Main and Sanchez-Pena, 2015). Although the summary statistics showed differences in the average MGUDS-S scores between domestic and international engineering graduate students, this difference is attenuated once other factors are considered.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Model 1, which includes all 390 students, indicates that female students are more likely to score higher than male students by 2.9 points on the MGUDS-S total score. This is consistent with previous research that found differences in intercultural competency scores by gender at the undergraduate level (Jesiek et al , 2012; Main and Sanchez-Pena, 2015). Although the summary statistics showed differences in the average MGUDS-S scores between domestic and international engineering graduate students, this difference is attenuated once other factors are considered.…”
Section: Resultssupporting
confidence: 93%
“…Thus, this study contributes to the literature and to discussions on promoting intercultural competency among scientists and engineers by examining the intercultural competency levels among engineering doctoral students. It extends Main and Sanchez-Pena’s (2015) study on engineering undergraduate students by focusing on doctoral students and how previous travel and language experiences are associated with intercultural competency. By focusing on graduate students in engineering, this study provides insights on the factors related to fostering interculturally competent engineers toward facilitating productive international science and engineering collaborations.…”
Section: Literature Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…In the study [7] author proposed a conceptual model explaining the factors that influence global competency levels, and also identifies the baseline levels of global competency for benchmarking. The study also focused to evaluate how participation in study abroad programs, international experiences, culturally-relevant curricula, and other related activities can contribute to changes in students' ability to work in diverse environments.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…There are several instruments developed to measure cultural competency in different contexts and dimensions. One such instrument is the Miville-Guzman Universality-Diversity Scale (M-GUDS) which measures the cultural competency using the construct Universal-Diverse Orientation (UDO) -"an attitude of awareness and acceptance of both the similarities and differences among people" [7]. Originally developed as 45-item scale, but later shortened to 15items (M-GUDS-S) measure UDO in three factors -Diversity of contact (behavioral): interest in participating in diverse and internationally focused activities of social and cultural nature; Relativistic Appreciation (cognitive): appreciation of similarities and differences in people;…”
Section: Cultural Competency and M-gudsmentioning
confidence: 99%